A CFD‐DEM approach to study the breakup of fractal agglomerates in an internal mixer. (22nd June 2020) - Frungieri, Graziano; Boccardo, Gianluca; Buffo, Antonio; Marchisio, Daniele; Karimi‐Varzaneh, Hossein Ali; Vanni, Marco
Abstract: In this work we present a method to investigate the breakup of filler agglomerates in an internal mixer during a compounding operation. The method employs computational fluid dynamics (CFD) simulations along with discrete element method (DEM) simulations. CFD simulations are performed to compute the flow field inside a 2D section of a typical batch internal mixer with two tangential rotors. During the CFD simulation, we assume the filler agglomerates to behave as tracer particles, carried passively by the flow. The trajectory of the tracers, together with the experienced velocity gradients, are fed to a DEM code, built in the framework of Stokesian dynamics. The code computes the mechanical response of the agglomerates along the trajectory, from which it is finally possible to ascertain the occurrence of breakup. Simulations are performed to evaluate the robustness of the method on two different rotor speed ratio conditions and varying agglomerate strength.